Nilai-Nilai Hukum Laut Amanna Gappa Dalam United Nations Convention On The Law Of The Sea (UNCLOS) (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Amanna Gappa is the third Matoa of Wajo. He formulated a maritime law known as Amanna Gappa, which was enacted in 1676. This law discusses the rules for trading and sailing during that time. Three hundred years later, a modern maritime law was established, known as the United Nations Convention on the Law of the Sea (UNCLOS). The research method used is qualitative research utilizing secondary data through literature studies such as documents, articles, reports, scientific journals, and internet sites. The collected data is then analyzed to produce descriptive information presented by the author in the form of sentences and words that support explanations related to the research.The laws within Amanna Gappa's maritime law consist of 21 articles and cover various matters, both technical and non-technical. It outlines efforts to achieve welfare on board ships, detailing the rights and obligations of everyone involved. This is quite similar to UNCLOS; however, its orientation is more towards the state, focusing on how UNCLOS seeks to regulate national welfare at sea. The values that continue to be upheld in current maritime law emphasize that regulations should be made as much as possible for the sake of welfare and justice. Moreover, both ancient and contemporary maritime laws prioritize common interests through deliberation in establishing these rules.